Substitution between Foreign Capital in China, India, the Rest of the World, and Latin America: Much Ado about Nothing? - Cravino, Javier; Lederman, Daniel; Olarreaga, Marcelo (2012)
This paper explores the impact of the emergence of China and India on Foreign Capital Stocks (FCS) in other economies. Using bilateral FCS data from 1990-2003 and drawing from the Knowledge-Capital Model of multinational enterprises to control for fundamental determinants of FCS across countries, the evidence suggests that the impact of foreign capital in China and India on other countries' FCS has been positive. This finding is robust across different specifications and estimation techniques. There is surprisingly weak evidence of substitution in manufacturing FCS away from Central America/Mexico in favor of China, and from Southern Cone countries to India, but these findings are not robust to the use of alternative estimation techniques. In sum, fears of a global competition for FDI seem misplaced, and policymakers concerned about attracting foreign investors should focus their efforts on the fundamentals determinants of FDI.